Diabetes mellitus in the context of COVID-19 - Carlos Enrique Medina Campaña; Elizabeth Hernández González (Universidad de Ciencias Médicas de Granma, 2020)
A high prevalence of diabetes mellitus (DM) represents a challenge during the coronavirus disease 2019 (COVID-19) pandemic. DM represents an important risk factor for adverse outcomes in patients with COVID-19. Objective: to describe the clinical, epidemiological and molecular characteristics; including treatment options among patients with COVID-19 and diabetes mellitus. Method: a literature review was conducted in articles published by peer-reviewed journals up to June 2020. SciELO and PubMed databases were screened in search of articles. The search terms included diabetes mellitus, coronavirus infection, and its Spanish translation "diabetes mellitus", "infección por coronavirus". Development: COVID-19 and diabetic patients may be predisposed to immune dysfunction that results in severe late illness. Most patients with mild infection can continue with the usual antihyperglycemic medications. The result of the use of corticosteroids is not yet clear. There are safety concerns regarding treatment with chloroquine/hydroxychloroquine, due to its hypoglycemic role and adverse effects. Conclusions: the molecular and pathophysiological mechanisms between COVID-19 and diabetes mellitus are still not fully understood. The poor prognosis observed in these patients requires the creation of a novel treatment protocol.